1993
DOI: 10.1002/pro.5560021119
|View full text |Cite
|
Sign up to set email alerts
|

Application of molecular dynamics and free energy perturbation methods to metalloporphyrin‐ligand systems ii: Co and dioxygen binding to myoglobin

Abstract: The protein contribution to the relative binding affinity of the ligands CO and O2 toward myoglobin (Mb) has been simulated using free energy perturbation calculations. The tautomers of the His E7 residue are different for the oxymyoglobin (MbO2) and carboxymyoglobin (MbCO) systems. This was modeled by performing two‐step calculations that mutate the ligand and mutate the His E7 tautomers in separate steps. Differences in hydrogen bonding to the O2 and CO ligands were incorporated into the model. The O2 comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…Although the interaction of Fe bound CO with the protein is expected to be weaker because of a less favorable geometry, the Fe-C-O unit itself is more polarizable; it is therefore plausible that the presence, or otherwise, of the distal side chain can account for the observed shifts in the vco frequency of the A states. Lopez and Kollman (1993) have recently found a 0.74 kcal/mol free energy difference between the two distal histidine tautomers of MbCO, suggesting, as found here, that there are significant differences in the distal-CO interaction between the two tautomers. Their calculation was performed, however, in vacuo, and their result is subject to a large error (±0.78 kcal/mol).…”
Section: Comparison With Crystal Structuressupporting
confidence: 81%
See 1 more Smart Citation
“…Although the interaction of Fe bound CO with the protein is expected to be weaker because of a less favorable geometry, the Fe-C-O unit itself is more polarizable; it is therefore plausible that the presence, or otherwise, of the distal side chain can account for the observed shifts in the vco frequency of the A states. Lopez and Kollman (1993) have recently found a 0.74 kcal/mol free energy difference between the two distal histidine tautomers of MbCO, suggesting, as found here, that there are significant differences in the distal-CO interaction between the two tautomers. Their calculation was performed, however, in vacuo, and their result is subject to a large error (±0.78 kcal/mol).…”
Section: Comparison With Crystal Structuressupporting
confidence: 81%
“…Only recently has a detailed force field been developed for the haem prosthetic group of the globin proteins (Kuczera et al, 1990), and a number of calculations have been published concerning the photodissociation dynamics of a CO ligand (considering the 64N8H tautomer and the 64His+ distal residues) (Straub and Karplus, 1991;Petrich et al, 1991), the vacuum dynamics of 64N,H MbCO (Kuczera et al, 1990;Henry, 1993), and the diffusion of ligands through the protein (Elber and Karplus, 1990). The free energy difference between the two distal histidine tautomers of neutral pH MbCO has also been recently considered (Lopez and Kollman, 1993). In this study, a total of four 90 ps trajectories have been calculated, differing in primary structure only in the protonation site of the distal histidine side chain, which is shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Accurate molecular mechanics potentials can estimate changes in the global protein energy on CO binding [40,41]. Improved understanding of the heme-CO energetics and increasingly precise structural information should provide the guidance needed for a quantitative theoretical evaluation of steric inhibition of CO binding in heme proteins.…”
Section: Steric Control Of Co Bindingmentioning
confidence: 99%
“…1), since the Fe ) O distance , is much greater than the C-O distance. In a later molecular mechanics calculation, Lopez and Kollman [34] optimized the MbCO geometry, and calculated a 67 tilt and an Fe-C-O angle of 174 or 1607, depending on the assumed tautomer of the distal histidine. Both these calculations used FeCO force constants transferred from the Cr(CO) 6 molecule, but Li and Spiro [18] found that a substantially higher FeCO bending constant was required to fit the ob- Fig.…”
Section: How Much Energy?mentioning
confidence: 99%